Pengaruh Perputaran Kas Dan Perputaran Persediaan Terhadap Return On Asset (Roa) PT Industri Jamu Dan Farmasi Sido Muncul Tbk Periode 2015- 2024 - Nurhaipah, Siti; Nurhamdi, Muhamad (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of cash turnover and inventory turnover on Return on Assets (ROA) at PT Industri Jamu dan Farmasi Sido Muncul, Tbk for the period 2015-2024. The method used in this study is a descriptive quantitative method. The source of this research is secondary data. The population of this study is the annual financial report of PT Industri Jamu dan Farmasi Sido Muncul Tbk, for the period 2015-2024 over a period of 10 years. The data analysis method used in this study is descriptive statistical test, classical assumption test, multiple linear regression analysis test, correlation coefficient test, hypothesis test (t test and F test), and determination coefficient test in SPSS software processing version 26. Based on the partial test analysis of the cash turnover variable on Return On Asset (ROA) there is a positive influence with a calculated t value of 4.318> t table 2.365 and a significant value of 0.003 <0.05, for the inventory turnover variable on Return On Asset (ROA) partially there is no influence with a calculated t value of 1.600 <t table 2.365 and a significant value of 0.154 > 0.05. Simultaneous test analysis between cash turnover and inventory turnover on Return On Asset there is an influence with the results of F count 21.237 > F table 4.46 and a significant value of 0.001 <0.05. The coefficient of determination is 81.8%, with the remaining 18.2% explained by variables outside the studied model.